The Degree of Mental Health of Boarding School Students Based on Islamic Psychoeducation - Machfudz (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2024)
The article analyzes the students' mental health level and the administrators' role in counseling assistance through psychoeducation techniques at the Raudhatul Jadid Islamic Boarding School, Lumajang. The design in this research uses mixed based on problems viewed from different perspectives. Based on the research results, the higher the emotional and psychological well-being level, the higher the dimensions of social well-being they felt, and vice versa. The psychoeducation technique with Islamic values used to build the mental health of students at the Raudhatul Jadid Lumajang Islamic Boarding School is the group organization method by forming a male and female student council. Whenever a problem arises with the students, it will first be handled by the male/female student council. Second, an external technique uses tools that can be seen, heard, and felt by students/counselees.